3D RC beam–column joints retrofitted by joint enlargement using steel angles and post-tensioned bolts. (1st October 2020) - Maddah, Armin; Golafshar, Ali; Saghafi, Mohammad Hossein
Highlights: Four exterior 3D concrete beam-column joint specimens with scale of 1/2 were constructed. Two specimens retrofitted using angles and post-tensioned bolts. Evaluation of the results demonstrates the efficiency of the retrofit system in enhancing the cyclic behavior of the joints. The retrofit method relocated the plastic hinge from the column face to outside of the joint core. Abstract: The performance of moment frames in concrete structures is influenced by the behavior of beam-column joints. Experience in past earthquakes has shown that beam-column joints with non-seismic details are highly vulnerable due to the lack of details and transverse reinforcement intervals in the joint core; furthermore, the brittle failure in joints of such type causes overall structural destruction. The present paper focuses on the seismic retrofitting of 3D exterior beam-column joints with no seismic details and considering the effect of slab and transverse beam. For this purpose, four exterior 3D concrete beam-column joint specimens with a scale of 1/2 were constructed and subjected to cyclic loading. The tested specimens comprised two control specimens with and without special seismic details; the two other specimens were retrofitted using angles and post-tensioned bolts. Noteworthy, the effect of initial damage on the cyclic behavior of one of the specimens with retrofit system was further taken into account. All specimens were compared in terms of hysteresis curves and other such parameters as strength, energy dissipation, stiffness reduction, equivalent hysteretic damping, and cracking pattern. The results indicated the efficiency of the retrofit system in enhancing the cyclic behavior of the joints, due to the relocation of shear hinge from the joint core and the formation of flexural plastic hinge in the beam.